2006
DOI: 10.1128/aac.50.4.1463-1469.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Farnesol on Staphylococcus aureus Biofilm Formation and Antimicrobial Susceptibility

Abstract: Staphylococcus aureus is among the leading pathogens causing bloodstream infections able to form biofilms on host tissue and indwelling medical devices and to persist and cause disease. Infections caused by S. aureus are becoming more difficult to treat because of increasing resistance to antibiotics. In a biofilm environment particularly, microbes exhibit enhanced resistance to antimicrobial agents. Recently, farnesol was described as a quorum-sensing molecule with possible antimicrobial properties. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
246
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 304 publications
(265 citation statements)
references
References 42 publications
(81 reference statements)
6
246
1
3
Order By: Relevance
“…These data indicated that low concentrations of farnesol were sufficient to exhibit antibacterial effect, as was demonstrated by viability assays. For Staphylococcus aureus this was observed in the presence of 200 lM (44 lg ml -1 ) farnesol [6]. This inhibitory effect can be due to the hydrophobic nature of farnesol that favours its accumulation in the membrane, possibly causing membrane disruption [6].…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…These data indicated that low concentrations of farnesol were sufficient to exhibit antibacterial effect, as was demonstrated by viability assays. For Staphylococcus aureus this was observed in the presence of 200 lM (44 lg ml -1 ) farnesol [6]. This inhibitory effect can be due to the hydrophobic nature of farnesol that favours its accumulation in the membrane, possibly causing membrane disruption [6].…”
Section: Resultsmentioning
confidence: 93%
“…For Staphylococcus aureus this was observed in the presence of 200 lM (44 lg ml -1 ) farnesol [6]. This inhibitory effect can be due to the hydrophobic nature of farnesol that favours its accumulation in the membrane, possibly causing membrane disruption [6]. In fact, exposure to terpene alcohols has been recently shown to affect the cell membranes of S. aureus, Escherichia coli and Listeria monocytogenes, resulting in leakage of K ?…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations